Investigation of factors that affecting job performance in banking sector / Saidatul Aqmar Mohd Nazri and Elwana Adnan - Mohd Nazri, Saidatul Aqmar; Adnan, Elwana (2014)
The study purpose is to determine job performance in banking sector. It is useful to know what are the most factors that affect job performance in banking sector. For this research, researcher analyze three influence factor that affecting job performance in banking sector which are rewards, motivation, recognition and stress. 150 respondents from iCIMB Bank and Al-Rajhi Bank were chosen and questionnaires were distributed to both banks. The result shows that motivation is the strongest influence on job performance, followed by recognition, reward and stress. However, for stress has weak effect on job performance. The researchers recommended to the organizations to set realistic performance goals, improve reward system, and creating a friendly work environment to improve the job performance.